The role of ZAP and OAS3/RNAseL pathways in the attenuation of an RNA virus with elevated frequencies of CpG and UpA dinucleotides - Odon, V; Fros, JJ; Goonawardane, N; Dietrich, I; Ibrahim, A; Alshaikhahmed, K; Dung Nguyen; Simmonds, P (Oxford University Press, 2019)
Zinc finger antiviral protein (ZAP) is a powerful restriction factor for viruses with elevated CpG dinucleotide frequencies. We report that ZAP similarly mediates antiviral restriction against echovirus 7 (E7) mutants with elevated frequencies of UpA dinucleotides. Attenuation of both CpG- and UpA-high viruses and replicon mutants was reversed in ZAP k/o cell lines, and restored by plasmid-derived reconstitution of expression in k/o cells. In pull-down assays, ZAP bound to viral RNA transcripts with either CpG- and UpA-high sequences inserted in the R2 region. We found no evidence that attenuation of CpG- or UpA-high mutants was mediated through either translation inhibition or accelerated RNA degradation. Reversal of the attenuation of CpG-high, and UpA-high E7 viruses and replicons was also achieved through knockout of RNAseL and oligodenylate synthetase 3 (OAS3), but not OAS1. WT levels of replication of CpG- and UpA-high mutants were observed in OAS3 k/o cells despite abundant expression of ZAP, indicative of synergy or complementation of these hitherto unconnected pathways. The dependence on expression of ZAP, OAS3 and RNAseL for CpG/UpA-mediated attenuation and the variable and often low level expression of these pathway proteins in certain cell types, such as those of the central nervous system, has implications for the use of CpG-elevated mutants as attenuated live vaccines against neurotropic viruses.